Urgensi Perlindungan Hak Cipta Atas Lagu Yang Diunggah Tanpa Izin di Media Sosial - Ahmad Aqil Dzakki Bintang Kurniawan; Aaron Yaman Ardiantra; Fadhillah Amirul Ikhsan (International Forum of Researchers and Lecturers, 2024)
Copyright is the legal right that inherently belongs to the creator of a work once it is expressed in a tangible form, and it cannot be limited unless specified by the law. Music and songs are forms of intellectual property that should be registered with the Directorate General of Intellectual Property (DJKI). Song copyright is a legal privilege that musicians can get by creating a piece of art in the form of music and songs. Songs are a form of intellectual property that is safeguarded under Law Number 28 of 2014. With the advancement of highly advanced technology, it becomes more convenient for individuals to enjoy songs or music through an application. Nevertheless, several cover versions continue to be posted without obtaining consent from the original creator. This text seeks to determine if a creator, whose song has been uploaded by a third party, is entitled to legal protection. Additionally, it intends to explore the legal ramifications for individuals who upload a song without the author's consent. The author employs normative research methodologies in this study, analyzing legal resources such as statutory rules, legal theory provisions, and expert opinions. According to Article 5 and Article 9 of Law Number 28 of 2014 about Copyright, creators are granted legal protection for music that are uploaded by third parties, regardless of the medium used to announce the song. This protection applies universally, regardless of location.